4m-3n=8form

Simple and best practice solution for 4m-3n=8form equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4m-3n=8form equation:


Simplifying
4m + -3n = 8form

Solving
4m + -3n = 8fmor

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-8fmor' to each side of the equation.
4m + -8fmor + -3n = 8fmor + -8fmor

Reorder the terms:
-8fmor + 4m + -3n = 8fmor + -8fmor

Combine like terms: 8fmor + -8fmor = 0
-8fmor + 4m + -3n = 0

Add '3n' to each side of the equation.
-8fmor + 4m + -3n + 3n = 0 + 3n

Combine like terms: -3n + 3n = 0
-8fmor + 4m + 0 = 0 + 3n
-8fmor + 4m = 0 + 3n
Remove the zero:
-8fmor + 4m = 3n

Combine like terms: 3n + -3n = 0
-8fmor + 4m + -3n = 0

The solution to this equation could not be determined.

See similar equations:

| 7x+263.5=2717 | | 5b+3(b-4)=2(y+3) | | 3x+6(-2)=24 | | 0.6x+1.9=5 | | 5b+3(b-4)=2(y+2) | | -25x+1+10=10z+1 | | 5b+3(3-4)=2(y+2) | | 1.8c+32=39.2 | | 1.5x+3.4=7.9 | | y=2x+75 | | 5b+3(b-4y)=2(y+2) | | -5u+2=12 | | 5b+3(3-4y)=2(y+2) | | 11=2h+3 | | 6x-15=4x+30 | | -2(q-29)=0.5(4-q) | | -2(-5+1)+1=-10 | | 3y-9=6y+9 | | 0.05=B^24 | | s=gt(gt) | | (-2x^2+12x)=0 | | (-x^2-11x)=0 | | 50+2x-1+6x+11=180 | | 2(j+4)-2=2 | | 3(g-7)=6 | | 10-b=4 | | 7m+4-5m=-2+m-9 | | -1+3x=3+9x | | 4=2(g-6) | | 5x-3x=8+2 | | (3x-6)(2x-9)= | | -3+4(x-1)=13x+6-9x |

Equations solver categories